A Novel Mutation of the HNF1B Gene Associated With Hypoplastic Glomerulocystic Kidney Disease and Neonatal Renal Failure: A Case Report and Mutation Update. Issue 7 (February 2015) - Alvelos, Maria Inês; Rodrigues, Magda; Lobo, Luísa; Medeira, Ana; Sousa, Ana Berta; Simão, Carla; Lemos, Manuel Carlos
Abstract : Abstract: Hepatocyte nuclear factor 1 beta ( HNF1B ) plays an important role in embryonic development, namely in the kidney, pancreas, liver, genital tract, and gut. Heterozygous germline mutations of HNF1B are associated with the renal cysts and diabetes syndrome (RCAD). Affected individuals may present a variety of renal developmental abnormalities and/or maturity-onset diabetes of the young (MODY). A Portuguese 19-month-old male infant was evaluated due to hypoplastic glomerulocystic kidney disease and renal dysfunction diagnosed in the neonatal period that progressed to stage 5 chronic renal disease during the first year of life. His mother was diagnosed with a solitary hypoplastic microcystic left kidney at age 20, with stage 2 chronic renal disease established at age 35, and presented bicornuate uterus, pancreatic atrophy, and gestational diabetes. DNA sequence analysis of HNF1B revealed a novel germline frameshift insertion (c.110_111insC or c.110dupC) in both the child and the mother. A review of the literature revealed a total of 106 different HNF1B mutations, in 236 mutation-positive families, comprising gross deletions (34%), missense mutations (31%), frameshift deletions or insertions (15%), nonsense mutations (11%), and splice-site mutations (8%). The study of this family with an unusual presentation of hypoplastic glomerulocystic kidney disease with neonatal renal dysfunction identified a previously unreported mutation of the HNF1B gene, thereby expanding the spectrum of known mutations associated with renal developmental disorders. Abstract : Supplemental Digital Content is available in the text